2022
DOI: 10.1039/d1ce01626a
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a correlation between ferroelectricity and grain sizes in Hf0.5Zr0.5O2 ferroelectric thin films

Abstract: The correlation between ferroelectricity and grain sizes in atomic layer deposition (ALD) derived Hf0.5Zr0.5O2 (HZO) thin films has been demonstrated through controlling process conditions. The influence of annealing temperature, annealing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…It has been reported that the ferroelectricity of HZO films is enhanced with smaller grain size. 15,52 Significantly, for conventional perovskite ferroelectric materials, massive grain size exhibits robust polarization. 56,57 This indicates that the mechanism of grain size effect in regulating the ferroelectricity of HZO films is completely different from that of conventional ferroelectric materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the ferroelectricity of HZO films is enhanced with smaller grain size. 15,52 Significantly, for conventional perovskite ferroelectric materials, massive grain size exhibits robust polarization. 56,57 This indicates that the mechanism of grain size effect in regulating the ferroelectricity of HZO films is completely different from that of conventional ferroelectric materials.…”
Section: Resultsmentioning
confidence: 99%
“…39 Apart from the use of different electrodes, the grain size can also be modulated by other methods. For example, Chen et al 15 experimentally studied the effects of the annealing process (annealing temperature and annealing time) on the grain size, furthering accurate modulation of HZO thin films ferroelectric properties from 5 to 25 μC/cm 2 . Moreover, Chen et al compared the effect of high-temperature ALD (300 °C) and low-temperature ALD (200 °C) on grain size, demonstrating that the low-temperature deposition process brings profitable gains in polarization value, breakdown voltage, and frequency response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroelectrics based on hafnia, such as doped HfO 2 and Hf 0.5 Zr 0.5 O 2 , are quite unusual compared with conventional perovskite ferroelectrics. First of all, though these oxides consist of mixed ionic-covalent bonding, it is unclear whether the covalence should play any role in the ferroelectricity. On the other hand, in perovskite oxide ferroelectrics, the existence of orbital hybridization and covalent bonding is important for the ferroelectric distortion .…”
Section: Introductionmentioning
confidence: 99%